Transformations and Sustainability of Individual Housing in the city of Djelfa - Abdellaoui, Nabila Latifa; Benidir, Fatiha (Technium Social Sciences Journal, 2022)
The present study aims to shed light on the residential transformations taking place at the level of traditional individual housing and the extent to which they achieve the sustainable dimension of housing in the Algerian city of Djelfa. The latter has undergone design, functional, morphological, and structural changes in addition to transformations within different time periods. In order to accommodate their evolving housing demands and requirements, inhabitants translated these manifestations through their practices and interventions, sometimes outside of the legal framework and sometimes in a traditional method. In order to achieve the required goals, we employed one of the field investigation instruments, kind observation, and the questionnaire given to the neighborhood people, within a 10% study sample that was discovered and chosen for numerous aspects. This study’s significance lies in knowing the relationship between the degree of housing transformation and the sustainable feature; achieving the sustainability and continuity of housing through morphology, construction, and aesthetics.